Agroecological certifications and commercialization channels: a look under the eco-innovation shield - Regina Stroparo , Telma; Floriani, Nicolas (Seven Editora, 2023)
With the objective of discussing the insertion of agroecological products in commercialization channels, this article links principles of eco -innovation to the production and certification of products and processes arising from family farming. It presents a new territoriality, where networks of farmers are formed and, through social organization, there is certification by peers and consequent use of seals, attesting to the quality of what is sold. In the meantime, agroecology, participatory certification systems, eco -innovation, social innovation, networks, markets and commercialization channels are discussed. Methodologically, it is a qualitative research of a theoretical nature that seeks critical reflection on the subject. The results point to the growing problematization of the forms of appropriation, by various social actors, of agroecological knowledge through instrumental ( techno- scientific ) and economic rationality, conditioning the autonomy and creativity of the local socio-productive system to those logics. On the other hand, the establishment of alternative networks for joint sales, whether with the appropriation of new technologies - such as applications and/or websites, implies, above all, in changing paradigms not only in agroecology, but also on the part of consumers who adhere to a new social behavior. DOI: 10.56238/pacfdnsv1-052